1981
DOI: 10.1038/bjc.1981.152
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of mammary carcinoma cells in marrow smears using antisera to epithelial membrane antigen

Abstract: Summary.-We have developed a technique for the immunocytochemical staining of marrow smears using antiserum to epithelial membrane antigen (EMA). This membrane component is confined to, but widely distributed in, epithelial tissues and tumours derived from them, and is strongly expressed by infiltrating breast carcinoma cells. Marrow aspirates from patients with both early and metastatic breast cancer have been examined, and the results of immunocytochemical staining compared with conventional cytology and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
49
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(50 citation statements)
references
References 11 publications
0
49
0
1
Order By: Relevance
“…An immunohistochemical stain for EMA can identify minute metastatic deposits of carcinoma in organs such as liver and bone marrow (Sloane et al, 1980;Dearnaley et al, 1981). Our most recent studies have shown that EMA positive cells can be found in the marrows of approximately one third of patients at the time of surgery for a primary breast cancer (Dearnaley et al, 1983).…”
mentioning
confidence: 99%
“…An immunohistochemical stain for EMA can identify minute metastatic deposits of carcinoma in organs such as liver and bone marrow (Sloane et al, 1980;Dearnaley et al, 1981). Our most recent studies have shown that EMA positive cells can be found in the marrows of approximately one third of patients at the time of surgery for a primary breast cancer (Dearnaley et al, 1983).…”
mentioning
confidence: 99%
“…Antisera to EMA have been used for the detection of bone marrow and lymph node metastases from breast carcinoma (Heyderman et al, 1979;Sloane et al, 1980a,b;Gugliotta et al, 1981;Dearnaley et al, 1981Dearnaley et al, , 1983Redding et al, 1983), and for identification of malignant cells in serous effusions Epenetos et al, 1982).…”
mentioning
confidence: 99%
“…It has been shown that immunocytochemical staining for EMA can detect very small numbers of breast cancer in bone marrow smears that appear normal by conventional haematological techniques (Dearnaley et al, 1981).…”
mentioning
confidence: 99%
“…Using this antibody to form rosettes 95-98% of marrow cells can be removed producing a smaller number of smears. We have compared the rosetting technique with density separation over lymphoprep previously described (Dearnaley et al, 1981 (Goding, 1976 (Beverley, 1980). Studies using cell-lines and human tissues had shown no crossreactivity with breast cancer or other epithelial tissues (Beverley, 1980 The marrow aspirate/RBC.SaM mixture, after removal of the Percoll cushion, was gently resuspended by inverting the tube 3 times.…”
mentioning
confidence: 99%
See 1 more Smart Citation